Identification and characterization of new human medium reiteration frequency repeats. - Jurka, J (1993)
We report nine new families of human medium reiteration frequency interspersed repetitive elements (MER elements). They were identified by computer-assisted analyses. Six of them were independently confirmed as repetitive families by DNA-DNA hybridization, and the number of elements for each of these families was estimated by plaque hybridization assay. The involvement of some of the reported MER elements in genetic rearrangements is demonstrated.